Synthesis and ionic conductivity of glass ceramics with general composition (2-х)Na2О : хМІ2О : 3CoО : 2P2O5 (х = 0 or 0.05, МІ – Li, K) - Strutynska, N.Yu.; Kuzmin, R.M.; Titov, Y.A.; Slobodyanik, M.S. (Physics and Chemistry of Solid State, 2024)
Glass ceramic samples with general composition: (2-х)Na2О : хМІ2О : 3CoО : 2P2O5 (х = 0 or 0.05, МІ – Li, K) were synthesized by melt method with subsequent annealing of homogeneous glass at a temperature of 650°C. According to powder X-ray diffraction data, monophase phosphates with the general composition Na4-хMІхСо3(PO4)2P2O7 which belong to the orthorhombic system (space group Pn21a) were obtained. The calculated cell parameters of prepared phosphates correlate with the size of the substituted alkali metal atom. The FTIR spectroscopy data confirm the presence of two anion types (РО4 and Р2О7) in the structure of crystalline phosphates. The ionic conductivity properties of the synthesized samples were investigated using impedance spectroscopy method. Analisys of results showed an increase of specific conductivity at the partial substitution of sodium atoms (0.1 Na→0.1Li) in an initial structure Na4Со3(PO4)2P2O7. The obtained results can be in future used in the preparation of solid electrolytes for sodium-ion batteries based on substituted glass ceramics with the composition Na4-хMІхСо3(PO4)2P2O7 with improved ion-conducting characteristics.